Implementasi Layanan Bimbingan Dan Konseling Dalam Mengatasi Kesulitan Belajar Menulis Siswa Kelas I Di SD Negeri 01 Tempuran, Simo, Boyolali Tahun Ajaran 2016/2017 - Istiqomah, Novia, Honest Ummi K, S.S., M. Hum (2017)
This study aims to describe the implementation of guidance and counseling services in overcoming learning difficulties of writing, identifying factors causing learning disabilities, identifying solutions to overcome learning difficulties. This type of research is qualitative research with case study design. Informants in this research are classroom teachers as mentors, principals and students with problems. Data collection techniques used were interviews, documentation and observation. Data were analyzed through data reduction measures, data presentation and conclusions. Technique examination of data validity is done by technique triangulation of source and technique. The results showed that 1) the implementation of guidance and counseling services in overcoming learning difficulties of writing are: a) learning service, teachers provide services during the learning process takes place, through the process of learning teachers guide students well. From the services that teachers provide can know the ability and development of children's learning, b) individual counseling services, services provided where classroom teachers provide face-to-face guidance directly to students who have problems. In providing classroom service the teacher does not distinguish the student's personal or the problems faced by the students, c) the group counseling service that is the service provided by the classroom teacher where the student with the problem is solved in group dynamics with the help of the teacher. The issues discussed are individual issues that arise within the group. Of the three services provided by the classroom teachers are given at the time home from school about 30 minutes. 2) the factors that cause learning difficulties to write backed by three factors include: from the child's self that is less attention at the time of the learning process takes place, the environment such as peers or the community environment in terms of association, especially family parents who pay less attention in developing the ability of children write. 3) solution to overcome learning difficulties of writing that is through group guidance, direct guidance or individual guidance, and communicate with parents of students.